Multi-Tube Helmholtz Resonator Based Triboelectric Nanogenerator for Broadband Acoustic Energy Harvesting - Zhang, Qiqi; Xi, Ziyue; Wang, Yawei; Liu, Ling; Yu, Hongyong; Wang, Hao; Xu, Minyi (Frontiers in Materials, 2022)
Acoustic energy, especially broadband low-frequency sound energy is part of the environmental mechanical energy acquisition cannot be ignored. Herein, a multi-tube parallel Helmholtz resonator-based triboelectric nanogenerator (MH-TENG) is investigated to reap sound energy in low-frequency noise environments. The designed MH-TENG consists of a modified Helmholtz resonator and a thin-film TENG transducer. The core materials of the TENG transducer are aluminum, FEP film, and carbon. To further clarify the influence of the modified Helmholtz resonator on the conversion performance of MH-TENG, the acoustic characteristics of the improved resonators are systematically studied. A series of experiments show that the multi-tube parallel Helmholtz resonator structure has a better sound wave collection effect. Meanwhile, the flexible film TENG can reduce the optimal output frequency of the device. The power generation performance and the bandwidth of the MH-TENG are significantly improved by adopting a multi-tube Helmholtz resonator. Within the frequency bandwidth range of 230 Hz, MH-TENG can effectively improve the efficiency of acoustic energy harvesting. 110 LEDs and an electronic thermometer can be powered by the sound-driven MH-TENG. In addition, the MH-TENG has a good capacitor charging performance, which is conducive to its application in ambient sound energy harvesting.